A new perspective on ecological vulnerability and its transformation mechanisms. Issue 1 (31st December 2022) - Hou, Kang; Tao, Wendong; He, Dan; Li, Xuxiang
ABSTRACT: Ecological vulnerability refers to the degree of ecosystem disturbance, system damage, and the ability of system restoration. Although case-specific evaluations of ecological vulnerability are progressing rapidly, they have been carried out mainly in areas with intensive human activities or in harsh natural environments. Using the Web of ScienceTM core collection, this review paper summarized studies on ecological vulnerability published from 2000 to 2022 and analyzed in depth major case studies. It was found that traditional ecological vulnerability research has been addressed largely in terms of assessment models, data processing models, and analysis of influencing factors, however there was a lack of research on the process of vulnerability transformation. Because the vulnerability transformation in a hierarchical vulnerability index system is regulated by multiple factors in a heterogeneous region, it is urgent to understand how the ecological vulnerability in a region evolves from one level to another over time. Therefore this paper put forward the new perspective of research, i.e., applying quantitative analysis to identification of regulating factors and exploring the mechanisms of ecological vulnerability transformation. This new perspective could assist in monitoring the complex spatiotemporal changes in ecological vulnerability and taking necessary measures to prevent from decline of ecological stability. Graphical abstract: uf0001